Konseling Pra-Nikah bagi Calon Pengantin Wali ‘Adhal (Studi Kasus Kantor Urusan Agama Kecamatan Bajubang Kabupaten Batanghari) - Hariadi, Muhamad; Yunus, Abdullah; Madyan, Madyan (JIGC (Journal of Islamic Guidance and Counseling), 2022)
BP4 (Marriage Advisory, Development and Preservation Agency) carries no small task and has big challenges regarding growing family problems, requiring human resources related to mediation, advocacy and marriage consultants. This aims to improve organizational services that are responsive to all marriage and family issues that arise in society, including prospective bridal couples who are not approved by one of their parents. To review this phenomenon, the researcher used a qualitative approach using data collection techniques in the form of observation, interviews and documentation. The research results showed that: (1) The role of BP4 (Marriage Advisory, Development and Preservation Agency) officers in providing pre-marital counseling guidance to the prospective bride and groom 'adhal in the KUA Bajubang District, Batanghati Regency is to carry out a pre-marital guidance training program for caten which includes eight materials, namely: marriage, munakahat, the science of the soul of marriage, human life, marriage and household problems, monotheism, ubudiyah, and how to reach my home, my heaven. (2) Factors inhibiting potential guardian 'adhal brides in counseling guidance by BP4 (Marriage Advisory, Development and Preservation Agency) officers at the KUA, Bajubang District, Batanghari Regency, include: the lack of accurate data regarding marriage, divorce and the factors causing it so that BP4 difficulties in finding effective ways to provide guidance and counseling, as well as resistance from adhal guardians. (3) The effectiveness of implementing pre-marital counseling guidance for prospective brides and grooms 'adhal guardians by BP4 (Marriage Advisory, Development and Preservation Agency) officers at the KUA Bajubang District, Batanghari Regency is quite optimal. This is indicated by data on the minimal number of divorce/talak cases in the Bahubang area, Batanghari Regency when compared to other districts.